2018
DOI: 10.3201/eid2410.180589
|View full text |Cite
|
Sign up to set email alerts
|

Influenza C Virus in Cattle with Respiratory Disease, United States, 2016–2018

Abstract: We identified influenza C virus (ICV) in samples from US cattle with bovine respiratory disease through real-time PCR testing and sequencing. Bovine ICV isolates had high nucleotide identities (≈98%) with each other and were closely related to human ICV strains (≈95%). Further research is needed to determine bovine ICV’s zoonotic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 11 publications
0
32
2
1
Order By: Relevance
“…This was the first report of influenza C virus (ICV) in Canadian cattle. Interestingly, the detections were from cattle without respiratory disease, which was inconsistent with the report from the United States that ICV was detected in cattle with respiratory disease (Zhang et al, ). Further investigation is needed to understand the impact of ICV infection in cattle.…”
Section: Discussioncontrasting
confidence: 76%
“…This was the first report of influenza C virus (ICV) in Canadian cattle. Interestingly, the detections were from cattle without respiratory disease, which was inconsistent with the report from the United States that ICV was detected in cattle with respiratory disease (Zhang et al, ). Further investigation is needed to understand the impact of ICV infection in cattle.…”
Section: Discussioncontrasting
confidence: 76%
“…Influenza C virus (ICV) is lesser known type of influenza virus that commonly causes cold-like symptoms and sometimes causes lower respiratory infection, especially in children <2 years of age [1]. ICV is mainly a human pathogen; however, the virus has been detected in pigs, dogs, and cattle, and rare swine-human transmission has been reported [2][3][4][5][6]. ICV seropositivity has been found to be as high as 90% by 7-10 years of age, suggesting that most people are exposed to influenza C virus at least once during childhood [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, a second orthomyxovirus, influenza C virus (ICV), was detected in cattle with BRD in the midwestern USA ( Zhang et al, 2018a , 2018b ). ICV was previously unknown to infect cattle, and it is uncertain how long ICV has existed in the cattle population.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the potential role of ICV in disease in cattle is in its infancy. ICV was first identified in animals with BRD ( Zhang et al, 2018a ), suggesting that ICV may have an associative role in BRD. However, a recent retrospect case-control metagenomics study of feedlot cattle respiratory tract samples found no association between cattle with BRD and corresponding samples with reads mapping to ICV ( Zhang et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%